Dosage optimization of voriconazole in children with haematological malignancies based on population pharmacokinetics. (7th November 2022) - Wu, Yun; Lv, Chunle; Wu, Dongni; Qi, Jianying; Cai, Rongda; Zhou, Siru; Li, Chengxin; Wei, Yinyi; Liu, Taotao
Abstract: What is Known and Objectives: Voriconazole has a complex pharmacokinetic profile and exhibits different pharmacokinetic characteristics in adults and children. Nevertheless, few studies have been conducted on the population pharmacokinetics (PPK) of voriconazole in children with haematological malignancies. This study aims to build a PPK model and propose a suitable voriconazole treatment scheme for children with haematological malignancies. Methods: We retrospectively collected 146 samples from 67 children aged from 1.08 to 17.92 years. The PPK model was established using nonlinear mixed effects modelling (NONMEM). Dosage simulations were conducted on the basis of the final model's covariates. Results and Discussion: Data were fully characterized by a one‐compartment model with first‐order absorption and elimination. The weight (WT), CYP2C19 phenotype, and Albumin (ALB) were notable covariates for clearance (CL). The typical values of CL, the volume of distribution ( V ), and oral bioavailability ( F ) were 2.29 L/h, 76 L, and 0.902, respectively. The proposed doses for different CYP2C19 genotypes were presented in this ranking: EM (extensive metabolizer) > IM (intermediate metabolizer) > PM (poor metabolizer). Furthermore, higher dosages for light WT patients were recommended while lower ALB levels required lower doses. The probability of achieving the target (PTA) for the recommended doses ranged from 72.2% to 99%. What is New and Conclusion: We successfully built a voriconazole PPK model for children with hematologic malignancies. Dosing regimens were developed for different patients based on the final model, which could enhance the rational use of voriconazole in children with haematological malignancies. Abstract : This is a population pharmacokinetic study of voriconazole in Chinese children with haematological malignancies. A population pharmacokinetic model was developed and evaluated. Based on the final model, appropriate administration regimens were recommended, which could enhance the rational use of voriconazole in children with haematological malignancies.